Compared extraction methods on the physicochemical properties, antioxidant activity, and optimization of enzyme‐assisted extraction of polysaccharides from Gynura medica. Issue 9 (26th June 2019) - Li, Fengwei; Chen, Ligen; Yu, Xiaohong
Abstract: The effects of hot water extraction (HWE), enzyme‐assisted extraction (EAE), ultrasonic‐assisted extraction (UAE), and ultrasonic‐enzyme‐assisted extraction (UEAE) methods on the extraction yield, physicochemical properties, and antioxidant activities of Gynura medica polysaccharides (GMPs) were investigated. The GMPs extracted by four methods were designated GMPs‐H, GMPs‐E, GMPs‐U, and GMPs‐UE, respectively. Meanwhile, the EAE method was further optimized by response surface methodology (RSM). The results showed that EAE and UEAE methods both markedly enhanced the yield of GMPs. Four kinds of GMPs possessed different physicochemical properties including molecular weight distributions and surface morphology. EAE had higher scavenging abilities for DPPH radical compared to other methods. The optimal conditions for GMPs were predicted to be cellulase amount of 155 (mg/g), extraction time of 48.4 min and pH of 7.9, with a predicted yield of 11.98%. Under the optimal conditions, the yield of polysaccharides was 12.03%, which matched the predicted value well. Practical applications: Enzyme‐assisted extraction (EAE) is an environmentally friendly method that can be used to improve the extraction of active ingredients from various natural sources. Our results demonstrated that EAE could enhance the extraction yield of polysaccharides which was the most important active ingredient. In addition, Gynura medica polysaccharides possess good antioxidant activity, which means that Gynura medica polysaccharides may be a novel source of natural antioxidant in functional food.